ASSESSMENT OF SECURITY MEASURES IN UNIVERSITIES FOR ENFORCEMENT OF INTEGRITY OF INFORMATION SYSTEMS IN KISUMU AND SIAYA COUNTIES, KENYA - Musyoka, Martin M. N.; Raburu, George; Yoga, Castro; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
An ICT policy safeguards Integrity of Information Systems and ensures business continuity. This study sought to assess the level of compliance by Universities to their ICT security policies by assessing the integrity pillar. Literature review on Integrity of Information Systems as well as international standards and regulations such as HIPAA, FERPA, SOX and ISO 270003 that touch on CIA was carried out. A cross-sectional survey study design incorporated selfadministered quantitative and qualitative research that was carried out in eight campuses within Kisumu and Siaya Counties. The survey was conducted on universities that gave authorization of the survey to go on. Stratified sampling method was used to arrive at the right population of respondents in the universities. The study targeted ten campuses within the two counties but only eight authorized the study. The findings of this study reveals that overall compliance ratings in the three key pillars of IT security were below 50% on compliance ratings with integrity at 30% This study contributes to policy, practice and theory at county and individual level in two ways. Firstly it came up with empirical data on state of compliance to ICT policies in universities and secondly it will provide the government and the institutions’ management with an objective profile of issues and a proactive approach that can solve the issues in cost effective manner.